Successful return to work of individuals with chronic pain according to health care providers: a meta-synthesis/Retorno bem-sucedido ao trabalho para indivíduos com dor crônica, segundo os profissionais de saúde: uma metassíntese - Magalhães, Lilian; Chan, Crystal; Chapman, Audrey Colleen; Majed, Lorna; Samigullina, Renata; Trninic, Dejana; Shaw, Lynn (Cadernos Brasileiros de Terapia Ocupacional, 2017)
Introduction: Chronic pain is a persistent disease that causes personal and social economic problems when individuals are unable to return to work. Objective: This meta-synthesis investigated the perspectives of health professionals on the best mechanisms (triggering change) and approaches to support people with chronic pain on return to work. Method: Peer-reviewed articles published until October 2017 were searched in databases such as PsycINFO, EMBASE, CINAHL and Pubmed. The search was based on three concepts: “chronic pain”, “return to work” and “therapist”. Six articles were analyzed. Meta-ethnography was used to synthesize data extracted from qualitative studies. Results: Five second-order interpretations were revealed: social interactions contribute to rehabilitation and can interrupt the return to work; inadequate coordination and excessive bureaucracy complicates the return to work; communication between worker and other stakeholders is critical for return to work; health professionals are not clear about their roles; the congruence between health professionals and the workers’perspectives and goals on return to work impacts the treatment and its outcomes. A posterior analysis produced two third-order syntheses: 1. the need for assertive communication to lay the groundwork for best practices; and 2. inadequate coordination in the current system complicates return to work in cases of chronic pain. Conclusion: Stakeholders and health professionals need to understand their roles and responsibilities to consistently set goals and action plans for return to work. Keywords: Chronic Pain, Return to Work, Health Personnel